Wedge Resection vs. Stereotactic Body Radiation Therapy for Clinical Stage I Non-small Cell Lung Cancer: A Systematic Review and Meta-Analysis - Peng, Lei; Deng, Han-Yu; Liu, Zhen-Kun; Shang, Qian-Wen; Huang, Kai-Li; Zheng, Qiang-Qiang; Li, Wen; Wang, Yun (Frontiers in Surgery, 2022)
Background Whether wedge resection or stereotactic body radiation therapy(SBRT) has better effectiveness in treatment of clinical stage I non-small cell lung cancer(NSCLC) patients remains unclear. Here we conducted the first meta-analysis to directly compare the survival outcomes of clinical stage I NSCLCs treated with wedge resection and SBRT. Methods We systematically searched studies from PubMed, Embase, and Corchrane Library up to October 1, 2021. Data for analysis mainly included overall survival (OS) and disease-free survival (DFS), which were obtained directly from the text results or calculated from the Kaplan–Meier survival curve. We used the standard random-effect model test (DerSimonian and Laird method) to analyze the pooled hazard ratios (HRs) and 95% confidence intervals (CIs). The Q-test and I2-test were used to assess heterogeneity. The stability of pooled HRs was examined by sensitivity analysis. Results Six retrospective studies with a total of 11813 clinical stage I NSCLCs who received wedge resection or SBRT were included. The results showed that patients receiving wedge resection had a significantly better OS (HR = 1.20, 95% CI = [1.07, 1.34], P = 0.002) than those with SBRT, but no significant difference of DFS(HR 1.53, 95% CI = [0.83–2.83], P = 0.17) was observed. There was no significant heterogeneity during our analysis, but there may be potential publication bias among these studies. Conclusions Our meta-analysis showed that clinical stage I NSCLCs treated with wedge resection had superior OS than those treated with SBRT. However, more prospective clinical trials should be well designed to evaluate the optimal treatment modality of early-stage NSCLCs.